Transformation of School Libraries into Resource Centers for Learning: Challenges and Obstacles for the Information Professional - Castrillo Sequeira, Rosalyn (2012)
In this essay, the author addresses the need to transform school libraries into resource centers for learning that invigorate the curriculum of schools. Government policies are mentioned to project the strengthening of school libraries in Costa Rica, and the Chilean experience is highlighted as a model for this transformation. Finally, some challenges and obstacles of the information professional against the renewal process are dealt with.